Understanding education in the face of socio-spatial inequalities in the Covid-19 pandemic: a memory in mini-tales based on the perception of students and teachers. (Research, Society and Development, 2021)
Education is an act of love and, consequently, of sensitivity and empathy, although the traditional method still prevails in classrooms in Brazil, this does not mean that human training should be absent from the process of teaching and learning. Reality shows us a country of diversity, but also of inequality, and this scenario was more evident during the Covid-19 pandemic. In this sense, this article aims to understand how the memory of students and teachers reflected in mini-tales demonstrates the resistance of education in the face of socio-spatial inequalities caused by the pandemic caused by the coronavirus (Covid-19). The methodology used was the writing of memories about the educational reality during the pandemic period, exposed and manifested in mini-tales by students and teachers of a public school in the city of Fortaleza-CE. The reports show that socio-spatial inequalities brutally affect the education of the most vulnerable classes, as in addition to the difficulties in accessing remote education, whether due to lack of technological resources and/or internet, they still need to deal with unemployment, hunger, domestic violence, illness, fear, anxiety and grief.